THE EFFECT OF PILATES EXERCISES ON MUSCLE ELECTRICAL ACTIVATION IN ADULTS WITH CHRONIC LOW BACK PAIN: A SYSTEMATIC REVIEW - Romão,Catarina Isabel Guerreiro (2022)
ABSTRACT Low back pain is one of the most prevalent orthopedic conditions, affecting around 70% to 80% of the world’s population at least once during their life times. Surface electromyography is an important tool for assessing the muscle function of the lumbar stabilizers. One of the best treatment options for patients with chronic low back pain (CLBP) is physical exercise, particular lyaerobic exercise and Pilates, as these can reduce short-term pain and disability, and improve balance. This review aims to identify the state of art regarding the benefits of pilates on the population with CLBP, evaluating changes in the muscular activation of the muscles of the lumbar region. Searches were conducted on the following databases: PubMed (Medline), Science Direct, Scopus, Web of Science, Cochrane, Ebsco and Scielo; including gray literature: Google Scholar, Grey Literature, Pro Quest Dissertations & Theses. The inclusion criteria were adults with low back pain for three months or more, with or without referred pain in the lower limbs; studies that used electromyographic variables; studies with a pain assessment measure at two different times; studies with physical exercise performed only using the Pilates method. Applying these criteria, the searches retrieved 439 abstracts. Of these, 44 articles were evaluated for eligibility, and three fulfilled the qualitative and quantitative synthesis criteria. The average methodological quality score on the Downs and Black checklist was 15 out of 28. It was therefore concluded that Pilates is an excellent option for the treatment of non-specific low back pain, promoting health and helping prevent low back pain among asymptomatic individuals. Level of evidence II; Systematic Review of Level II or Level I Studies with Discrepant Results.